PERAN BANK SYARIAH MANDIRI DALAM MENGEMBANGKAN WISATA HALAL - Djakfar, Inayatillah; Isnaliana, Isnaliana; Putri, Yossie Kenanga (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2021)
This study aims to see the role of Bank Syariah Mandiri Kcp Ulee Kareng in developing halal tourism in the city of Banda Aceh. This study uses a qualitative method using a descriptive analysis approach. This research uses primary data and secondary data, namely by conducting interviews and centering studies and documentation which is analyzed in several stages, namely editing data, classifying, reducing, presenting data, and finally verifying. The results showed that Bank Syariah Mandiri Kcp Ulee Kareng has a role in developing halal tourism, namely in the Culinary Business Sector, Travel Service Providers and Lodging Providers. The financing provided to business actors is the financing of Micro Businesses. With the financing provided by this institution to players in the halal tourism industry, it has an impact on improving the economic welfare of the people.